2015
DOI: 10.1186/s13054-015-0788-x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced age is associated with worsened outcomes and a unique genomic response in severely injured patients with hemorrhagic shock

Abstract: IntroductionWe wished to characterize the relationship of advanced age to clinical outcomes and to transcriptomic responses after severe blunt traumatic injury with hemorrhagic shock.MethodsWe performed epidemiological, cytokine, and transcriptomic analyses on a prospective, multi-center cohort of 1,928 severely injured patients.ResultsWe found that there was no difference in injury severity between the aged (age ≥55, n = 533) and young (age <55, n = 1395) cohorts. However, aged patients had more comorbidities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
83
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 47 publications
4
83
2
2
Order By: Relevance
“…These studies define complicated MODS using ''Time To Recovery,'' which incorporates all deaths into the ''complicated'' MODS category and may explain the propensity toward higher overall injury severity. Other studies identify advanced age as a potential driver of complicated MODS in non-TBI injured patients (14). Our study supports this, and we also show PRMODS to be associated with higher admission base deficit and transfusion requirements, both of which are implicated in immunosuppressive responses after trauma (8).…”
Section: Discussionsupporting
confidence: 79%
“…These studies define complicated MODS using ''Time To Recovery,'' which incorporates all deaths into the ''complicated'' MODS category and may explain the propensity toward higher overall injury severity. Other studies identify advanced age as a potential driver of complicated MODS in non-TBI injured patients (14). Our study supports this, and we also show PRMODS to be associated with higher admission base deficit and transfusion requirements, both of which are implicated in immunosuppressive responses after trauma (8).…”
Section: Discussionsupporting
confidence: 79%
“…Thus, return to homeostasis is a key objective for future immunomodulation therapy of elderly trauma and sepsis patients (33,34,41). However, it is clear that juveniles do not return to baseline genomic expression patterns after severe trauma within 3 days in this study.…”
Section: Discussionmentioning
confidence: 39%
“…We have previously demonstrated that, in response to injury, the elderly do not have an exaggerated inflammatory response nor greater suppression of adaptive immunity genes but, rather, a delayed return to baseline (33,34,41). Thus, return to homeostasis is a key objective for future immunomodulation therapy of elderly trauma and sepsis patients (33,34,41).…”
Section: Discussionmentioning
confidence: 99%
“…This "storm" (whether cytokine or genomic [27]) that occurs with severe infection or injury affects every aspect of mammalian biologymultiple molecules, genes, cells, tissues, compartments, and Mortality is increased significantly in the elderly in sepsis and trauma, and the incidence is increased in the former as well. Typical murine studies use animals that are the age equivalent of an adolescent human and thus, cannot reflect the majority of sepsis patients nor those at the greatest risk for poor outcomes after trauma [32][33][34]. Total circulating leukocyte comparisons…”
Section: Revision Rather Than Rejection Of Murine Modelsmentioning
confidence: 99%